2017
DOI: 10.18632/oncotarget.21246
|View full text |Cite|
|
Sign up to set email alerts
|

miR-29a-3p suppresses cell proliferation and migration by downregulating IGF1R in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), the most common primary tumor of the liver, has a poor prognosis and rapid progression. MicroRNAs (miRNAs) play important roles in carcinogenesis and tumor progression. Insulin-like growth factor 1 receptor (IGF1R) is a transmembrane heterotetrameric protein that has been reported to promote transformation to malignancy and cancer cell proliferation and survival. In this study, we found that the expression of miR-29a-3p was downregulated in HCC patients, resulting in poor surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…Many studies have demonstrated that miRNAs are involved in various biological processes of HCC, such as cell proliferation, invasion, migration, and the cell cycle [ 9 , 32 , 33 ]. Additionally, miRNAs can act as diagnostic and prognostic biomarkers in HCC [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that miRNAs are involved in various biological processes of HCC, such as cell proliferation, invasion, migration, and the cell cycle [ 9 , 32 , 33 ]. Additionally, miRNAs can act as diagnostic and prognostic biomarkers in HCC [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…HS6ST3 could promote breast cancer cell proliferation by upregulating IGF1R expression (29). It has been shown that IGF1R inhibits CCL5 expression and consequently reduces the chemotactic movement of CD8 + T lymphocytes (30). Taken together these findings suggest that through IGF1R, HS6ST3 could affect both CCL5 levels and tumor infiltrating CD8 + T lymphocytes behavior.…”
Section: Discussionmentioning
confidence: 84%
“…HS6ST3 encodes a member of Heparan sulfate (HS) involved in several cellular and molecular processes, including cell proliferation and differentiation (28). By regulating IGFR1 expression, HS6ST3 could affect CCL5 expression (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-16-5p was reportedly downregulated in breast cancer [76], hepatocellular carcinoma [77] and glioma [78], in agreement with our ndings. Overall, miR-29a-3p has been reported to function as a tumour suppressor and is downregulated in many types of cancers, such as thyroid carcinoma [32], colorectal carcinoma [79] and hepatocellular carcinoma [80].The downregulation of miR-34c-5p has been reported in several types of cancer, such as leukaemia [57] and osteosarcoma [58], and it has been closely associated with poor prognosis. Similarly, miR-490-5p is markedly downregulated in hepatocellular carcinoma tissues [81], in renal cell carcinoma tissues and cells [82] and in childhood neuroblastomas and cell lines [83].…”
Section: Discussionmentioning
confidence: 99%